Cameroon Country Opinion Survey Report (July 2013 - June 2014) - World Bank Group (Washington, DC, 2014)
The Country Opinion Survey for FY2013 in Cameroon assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Cameroon perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Cameroon on 1) their views regarding the general environment in Cameroon; 2) their overall attitudes toward the WBG in Cameroon; 3) overall impressions of the WBG s effectiveness and results, knowledge work and activities, and communication and information sharing in Cameroon; and 4) their perceptions of the WBG s future role in Cameroon.